A study on design and properties of woven-nonwoven multi-layered hybrid geotextiles. Issue 1 (June 2022) - Li, Ting-Ting; Zhou, Xiangyu; Wang, Zhike; Fan, Yuyang; Zhang, Xiayun; Lou, Ching-Wen; Lin, Jia-Horng
The area of forests continues decreasing while the water/soil loss becomes worse. In these complicated environments, mechanical properties, stability, high modulus and low elongation of geotextiles are required. On a premise of the acquisition of good mechanical properties and the improvement in the deformation and puncture resistance of nonwoven fabric, woven/nonwoven hybrid geotextiles are designed and made with needle punch processing technology in this study. The test results indicate that the mechanical properties of hybrid geotextiles are improved significantly when the areal density of nylon fabrics is increased. In particular, with the areal density of 400 g/m 2, hybrid geotextiles exhibit the maximal mechanical properties and puncture resistance. Moreover, the pore fraction of hybrid geotextiles decreases as a result of a rise in the areal density of nylon top/bottom layers. The use of a 3 D mesh fabric as the interlayer provides the needle punched composite geotextiles with the highest tensile resistance, puncture resistance. The composite geotextiles are treated with acid and alkali to simulate the corrosion under natural conditions of stabilized soil. The resultant geotextile has good mechanical properties and acid/alkali degradation resistance. This allows the hybrid geotextiles to stabilize water and soil conservation in complicated conditions.